Local immune dysregulation and subsequent inflammatory response contribute to pulmonary edema caused by Enterovirus infection in mice. Issue 2 (10th January 2023) - Sun, Tiantian; Li, Dong; Dai, Xinchen; Meng, Caiyun; Li, Yi; Cheng, Cheng; Ji, Wangquan; Zhu, Peiyu; Chen, Shuaiyin; Yang, Haiyan; Jin, Yuefei; Zhang, Weiguo; et al.
Abstract: Pulmonary edema that comes on suddenly is the leading cause of mortality in hand‐foot‐and‐mouth disease (HFMD) patients; however, its pathogenesis is still largely unclear. A range of research suggest immunopathogenesis during the occurrence of pulmonary edema in severe HFMD patients. Herein, to investigate the potential mechanism of immune dysregulation in the development of pulmonary edema upon Enterovirus (EV) infection, we established mouse infection models for Enteroviruses (EVs) including Coxsackievirus (CV) A6, Enterovirus A71 (EVA71), and CVA2 exhibiting a high incidence of pulmonary edema. We found that EVs infection induced an immune system disorder by reducing the numbers of pulmonary and circulatory T cells, B cells, macrophages, and monocytes and increasing the numbers of lung neutrophils, myeloid‐derived suppressor cells (MDSCs), and activated T cells. In addition, the concentrations of C−X−C motif chemokine ligand 1 (CXCL‐1), tumor necrosis factor‐alpha, monocyte chemoattractant protein‐1, and interleukin 6 were increased in EV‐infected lungs. Moreover, we found that EVs replication in mice lungs lead to apoptosis of lung cells and degradation of tight junction proteins. In conclusion, EVs infection likely triggered a complexed immune defense mechanism and caused dysregulation of innate immune cells (MDSCs, neutrophils, monocytes, and macrophages) and adaptive cellular immunity (B cells, T cells). This dysregulation increased the release of cytokines and other inflammatory factors from activated immune‐related cells and caused lung barrier damage and pulmonary edema.